MODERN MODELS OF EMERGENCY MANAGEMENT - Abdujalilova Malika Abu-Hasan qizi; Eshkuvatov Komil (Modern American Journals, 2025)
Contemporary models of emergency management incorporate advanced technology, data analytics, and collaborative frameworks to further enhance preparedness, response, recovery, and mitigation efforts. These models emphasize a multi-hazard approach, inter-agency coordination, community involvement, and the sharing of real-time information. This article looks into the evolution of emergency management, highlights contemporary strategies and tools, and discusses challenges and future prospects in the quest for improved resilience in the face of crises.
Keywords: Emergency management, disaster response, risk reduction, multi-hazard approach, real-time data, inter-agency cooperation, and community resilience.